Growth Performance of Silkworms (Tubifex sp.) Cultivated Using a Dry Substrate - Mhd Yazid; Iin Siti Djunaidah; Moch Nurhudah (Universitas Gadjah Mada, 2022)
Silkworms are one type of live food that has begun to be intensified in their cultivation activities in Indonesia. This study aimed to determine the effect of feeding/dried substrate in different doses on the growth performance of silkworms. The second aim was to determine the appropriate dose of dry substrate for silkworm cultivation. The study used a completely randomized design (CRD) with 4 treatments of dry media at a dose of 114 g/m2 (D10), 228 g/m2 (D20), and 324 g/m2 (D30) dan without media as a control (D0). With 3 replications for each treatment. A silkworm starter was obtained from cultivation for 30 days. The research was conducted at Warung Benih Farm in Depok for 33 days. Data were analyzed using Analysis of Variance (ANOVA) and Duncan's further test with a confidence level of 0.05. The results showed that absolute weight growth, population growth, and the best productivity were obtained in the treatment of substrate addition with a dose of 324 g/m2 (D30) with an absolute biomass growth of 48.67 g, population growth of 59458 individuals, & the productivity of 0.556 g/m2 was/cycle. Most of the water quality observations are in the relatively optimal range.